New prospects of vocational education and training - N. N. Aniskina (Высшее образование в России)
The article is focused on the key issues of vocational education and training (VET) reform in Russia. What is necessary for the transition from state regulation of vocational educationand training to market regulation? What should be VET development strategy under these circumstances? What are the problems of the legal regulation of VET? Organizational and methodical issues of quality assurance of vocational education and training and European experience in this sphere is considered in the article. Common Quality Assurance Framework (CQAF) for continuing education and training is also described.